Therapeutic potential and roles of dietary seaweeds in food: A systematic review - Beatrice M Fasogbon; Oluwaseun H Ademuyiwa; Oladeinde O. Ogundipe (World Development Sustainability, 2024)
Food security is a significant global concern as a result of the burden that the fast-expanding global population has placed on finite resources, such as arable land for farming. Additionally, the hunt for more nutritious food alternatives has been prompted by a growing understanding of health, nutrition, and diet. Seaweeds are simple-to-grow aquatic plants that are underused for food and medicine. Recent studies have focused on gaining access to and using these readily available natural resources for nutrition and medicinal objectives. This review systematically evaluated trends of recent research on seaweed, for therapeutic possibilities and product development. After examining several documents, this analysis discovered that seaweeds are incredibly beneficial algae for both nutrition and medicine, and may be further explored in innovative food products, in meeting the increasing global need for food.